Pemanfaatan Energi Biogas dan Pengoptimalan Tanah Berpasir untuk Tanaman Alternatif di Desa Garongan, Kecamatan Panjatan, Kabupaten Kulon Progo - Mayasari, Agatha (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Cows are one of the livestock that we often encounter. Meat and milk that produced by cows are used by humans as food. Garongan village, also utilizes cattle as one of the village's potential which is also a livelihood for the villagers. The large number of cattle in Garongan village also produces a lot of waste. However, there are still many of us who do not know that the waste from cows can be used as biogas energy which can be useful for daily life and of course reduce the existing waste. Besides the cattle, the villagers also use the sandy soil for farming. However, not all plants can grow well in sandy soil. Therefore, villagers only plant one type of plant on sandy soil, which is chili plants that are used for agriculture. However, besides chili, there are many alternative crops that can grow well on sandy soil and can be used as agriculture.